An Analysis of Kenyan Learners’ Proficiency in English Based on Reading Comprehension and Vocabulary - Athiemoolam, Logamurthie; Kibui, Agnes (Journal of NELTA, 2013)
In Kenya, English is the medium of instruction in schools and the official language of the country, although the majority of the learners are first additional language speakers of English. The study on which this article is based aimed to assess grade 10 Kenyan learners’ proficiency in English by examining their performance in comprehension and vocabulary on the basis of three tests incorporating multiple choice and interpretative questions. The data were collected from 422 grade 10 learners representing 16 schools in four provinces of Kenya. Learners were assessed on three comprehension passages which were selected from different genres. The results revealed that a large percentage of Kenyan learners encountered challenges with comprehension and vocabulary which impacted on their English language proficiency. The implications of the study is that there is a need for a reading skills development programme incorporating word analysis, recognition of the purpose of the text and tone, and the enhancement of inferential as well as predictive and interpretive skills. Journal of NELTA, Vol. 17 No. 1-2, December 2012, Page 1-13 DOI: http://dx.doi.org/10.3126/nelta.v17i1-2.8088